Paradigm shift : - Tapscott, Don (McGraw-Hill, 1993)
This easy-to-read, non-technical book examines and synthesizes the lessons of leading edge companies grappling with seven revolutionary IT changes. According to the authors, these changes have combined to create an entirely new paradigm for competitive information processing - now and for the future. This book zeros in on changes such as the shift from proprietary to open systems, from host-based to network-based systems, and stand-alone to integrated software applications.